Voltage SAG mitigation in power system using D-STATCOM for power quality improvement / Tengku Ahmad Faizal Tengku Majid - Tengku Majid, Tengku Ahmad Faizal (2013)
For some decades, power quality did not cause any problem, because it had no effect on most of the loads connected to the electric distribution system. When an induction motor is subjected to voltage sag, the motor still operates but with a lower output until the sag ends. With the increased use of sophisticated electronics, high efficiency variable speed drive, and power electronic controller, power quality has become an increasing concern to utilities and customers.